Spatiotemporal control of PIWI compartmentalization by mitochondrial scaffolds defines pachytene piRNA pathway organization - Xiaoyuan Yan; Chao Wei; Jeffrey M. Mann; Guanyi Shang; Qianyi Wang; Huirong Xie; Elena Y. Demireva; Liangliang Sun; Deqiang Ding; Chen Chen (Proceedings of the National Academy of Sciences, 2026)
Pachytene piRNAs are the least understood class of piRNAs in the mammalian male germ line. During meiosis, their biogenesis occurs near the mitochondrial outer membrane in germ granules known as intermitochondrial cement (IMC). However, how mitochondrial factors regulate the trafficking of PIWI proteins into and out of the IMC remain poorly understood. Here we show that the cytoplasmic PIWI proteins MILI and MIWI are recruited for pachytene piRNA biogenesis via distinct mitochondrial membrane proteins. Loss of the mitochondrial scaffold protein ASZ1 during meiosis in mice disrupts multiple downstream biogenesis steps, resulting in misregulation of MILI, MIWI, and MOV10L1, failure of IMC formation, and an almost complete loss of mature pachytene piRNAs. Strikingly, despite the drastic depletion of pachytene piRNAs, LINE1 transposon silencing remains unaffected. We identify three classes of pachytene piRNA pathway components that coordinate piRNA production and compartmentalization. Our findings reveal that chromatoid body precursors serve as a central hub for the accumulation of pachytene PIWI–piRNA complexes, thus establishing a connection between IMC-based biogenesis and downstream piRNA function.